Application of whole genome sequencing to the study of Pseudomonas aeruginosa - Naghra, H (2016)
The reduction in cost and increase in throughput of whole genome sequencing (WGS) technologies, and the advent of benchtop WGS instruments such as the Illumina MiSeq, means that WGS is no longer restricted to large genome centres and consortia. The number of microbial genomes in public repositories is ever increasing due to the availability of WGS technologies to research groups, with individual genera having their own dedicated genome databases. Pseudomonas aeruginosa is an opportunistic pathogen and a major cause of healthcare associated infection in immunocompromised individuals and cystic fibrosis (CF) patients. The first complete genome sequence of a P. aeruginosa strain was that of the most commonly studied laboratory strain P. aeruginosa PAO1, sequenced in 2000. It was found in a study, published in 2010, that there were differences between the chromosomal sequences of two isolates of P. aeruginosa PAO1 originating from two different public strain collections, as well as differences compared to the reference sequence. It was therefore proposed that P. aeruginosa PAO1 exists as variable sublines in strain collections, whose differences included a 2.2~Mb chromosomal inversion and a prophage insertion compared to the reference sequence, as well as single nucleotide polymorphisms (SNPs) and short insertions and deletions (INDELs) which are unique to individual sublines. Since the current genomic reference sequence is based on one of these variable sublines, this study aims to deduce the sequence of the original P. aeruginosa Strain 1 (PAO) from which all the PAO1 sublines are derived, using sequence information from several laboratory sublines and from P. aeruginosa strains PAO2 and PAO3, which were directly derived from the PAO progenitor strain. This could be used as a more universal reference which is representative of a range of PAO1 sublines, to which they are all more closely related.